Training and Installation of CCTV Security Systems at Putra Baitul Qur'an Islamic Boarding School Al-Khusyu Malang - Elka Faizal; Sugeng Hadi Susilo; Yuniarto Agus Winoko; Eko Yudiyanto; Umi Anis Roisatin; Agus Dani (Journal of Community Engagement, 2025)
The installation and training of CCTV security systems at Pondok Pesantren Putra Baitul Qur'an Al-Khusyu Malang aimed to improve both security and the technical skills of students. The training covered the basics of CCTV technology, including installation methods, system components, and maintenance procedures, enhancing students' knowledge and preparing them for the job market. The hands-on approach proved effective, as participants were actively involved in the installation and configuration of CCTV systems. Before the training, only a small percentage of students were familiar with CCTV technology, but post-training assessments showed a significant increase in knowledge. This program not only contributed to a safer environment within the pesantren but also provided valuable technical skills that students could use in their careers or entrepreneurship. Despite challenges such as limited resources and infrastructure, the training successfully empowered the students with skills relevant to modern security needs. This initiative sets a model for other educational institutions to integrate technical training with religious education, fostering a more skilled and competitive generation